Affordable housing in urban India: a review of critical success factors (CSFs) addressing housing adequacy with affordability for the urban poor. Issue 1 (31st December 2021) - Agarwal, Shagun; Singh, Tribhuvan Pratap; Bajaj, Deepak; Pant, Vimal
Abstract : Purpose: This paper aims to focus on the housing situation in Indian cities and the various stakeholders involved in the housing sector. This study addresses the conflict in expectations of the supply and demand side of the housing and establishes the factors crucial to making housing successful for all the stakeholders, essential for sustainable urban development. Design/methodology/approach: This paper is developed using the content analysis of preceding independent reviews on housing sustainability by authors across the globe, a review of the current housing situation in Indian cities and a Pilot study of the desired qualitative aspects of housing by the consumer group. Findings: This paper identifies the challenges and constraints of the various stakeholders involved in the housing sector. A comprehensive list of all the parameters, both qualitative and quantitative, essential for successful housing implementation, focused on the preferences of the demand side, also referred to as the "Critical Success Factors (CSFs)" is generated. The results advocate a strict consideration and integration of these CSFs with the housing policies for all future housing projects. Research limitations/implications: Most of the studies conducted in the past have reviewed the housing situation in India from the perspective of the government authorities and the initiatives undertaken by them to improve the housing crisis. However, a gap exists in achieving a balanced understanding of the supply-side constraints, with the demand-side expectations from the housing. Focusing only on the supply without adequately understanding the consumption can only lead to further chaos in the already turbulent housing situation. Originality/value: To the best of author's knowledge, this is among the first attempts to address the housing scenario in urban centers of India, simultaneously from the perspective of both the demand side and the supply side of the housing, giving additional impetus to the expectations of the demand side which are often ignored. This study becomes more relevant in the ongoing pandemic situation to be able to provide appropriate and acceptable housing solutions to all.